2012
DOI: 10.1095/biolreprod.112.099697
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Pathways Involved in Bovine Embryonic Genome Activation and Their Regulation by Alternative In Vivo and In Vitro Culture Conditions1

Abstract: Understanding gene expression patterns in response to altered environmental conditions at different time points of the preimplantation period would improve our knowledge on regulation of embryonic development. Here we aimed to examine the effect of alternative in vivo and in vitro culture conditions at the time of major embryonic genome activation (EGA) on the development and transcriptome profile of bovine blastocysts. Four different blastocyst groups were produced under alternative in vivo and in vitro cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
157
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(172 citation statements)
references
References 49 publications
9
157
1
5
Order By: Relevance
“…Further, to date there is no systematic study addressing the activation of specific genes during several stages of early bovine embryo development. Detailed insight into the time course of embryonic genome activation is important, because embryos are particularly susceptible during the period of EGA (e.g., to changing culture conditions) (7). However, the underlying mechanisms are only partially understood, and new molecular readouts, such as effects on the timing of EGA, are required.…”
mentioning
confidence: 99%
“…Further, to date there is no systematic study addressing the activation of specific genes during several stages of early bovine embryo development. Detailed insight into the time course of embryonic genome activation is important, because embryos are particularly susceptible during the period of EGA (e.g., to changing culture conditions) (7). However, the underlying mechanisms are only partially understood, and new molecular readouts, such as effects on the timing of EGA, are required.…”
mentioning
confidence: 99%
“…Some of the problems with the in vitro-produced embryo could result from selection of incompetent oocytes or inadequate oocyte maturation. However, the importance of the maternal environment during development is indicated by observations that transfer of in vitro-produced embryos to the oviduct after fertilization limits some of the abnormalities associated with in vitro production (9,21).…”
mentioning
confidence: 99%
“…For example, Dattena et al [192] confirmed higher sheep embryo cryosurvival results when including BSA and hyaluronan during IVC, and Gad et al [197] realized that altered culture conditions at different time points of the preimplantation period lead to adaptations of the embryos, changing their gene expression and developmental ability. As referred, the initial stages of development are those with higher cryosensitivity, from oocytes to late embryo, with the acquisition of cryotolerance in an intermediate stage of development.…”
Section: Methods Of Improving the Cryopreservation Of Sheep Embryosmentioning
confidence: 99%
“…Mitochondrial changes, namely, a reduced total number and an increase in the proportion of immature mitochondria [18,187], have been observed in poor-quality and IVP embryos and were associated with culture in serum-containing medium [210]. These changes have been also associated with inefficient lipid metabolism, with the presence of cytoplasmic vesicles and lipid drops and fewer lysosome-like vesicles [18], compromising ATP production [108,197,204].…”
Section: Methods Of Improving the Cryopreservation Of Sheep Embryosmentioning
confidence: 99%